Video games and rehabilitation: using design principles to enhance engagement in physical therapy - Lohse, Keith; Shirzad, Navid; Verster, Alida; Hodges, Nicola; Van der Loos, H F Machiel (Journal of neurologic physical therapy, 2013)
Patient nonadherence with therapy is a major barrier to rehabilitation. Recovery is often limited and requires prolonged, intensive rehabilitation that is time-consuming, expensive, and difficult. We review evidence for the potential use of video games in rehabilitation with respect to the behavioral, physiological, and motivational effects of gameplay. In this Special Interest article, we offer a method to evaluate effects of video game play on motor learning and their potential to increase patient engagement with therapy, particularly commercial games that can be interfaced with adapted control systems. We take the novel approach of integrating research across game design, motor learning, neurophysiology changes, and rehabilitation science to provide criteria by which therapists can assist patients in choosing games appropriate for rehabilitation. Research suggests that video games are beneficial for cognitive and motor skill learning in both rehabilitation science and experimental studies with healthy subjects. Physiological data suggest that gameplay can induce neuroplastic reorganization that leads to long-term retention and transfer of skill; however, more clinical research in this area is needed. There is interdisciplinary evidence suggesting that key factors in game design, including choice, reward, and goals, lead to increased motivation and engagement. We maintain that video game play could be an effective supplement to traditional therapy. Motion controllers can be used to practice rehabilitation-relevant movements, and well-designed game mechanics can augment patient engagement and motivation in rehabilitation. We recommend future research and development exploring rehabilitation-relevant motions to control games and increase time in therapy through gameplay.Video Abstract available (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A61) for more insights from the authors.